Hubungan Kepantasan Harga, Kepuasan Pelanggan DAN Loyalitas SERTA Harga yang Dapat Diterima - Raymond Setia Budi; Sabrina Oktoria Sihombing (Jurnal Ekonomi dan Bisnis, 2010)
The vast number of restaurant entrepeneur incite such an intense competitiveness whichleads to diversity in practising marketing strategy, One factor that needs to be brought into attention is pricing, which has become a sensitive subject in the time of global crisis.When something is overpriced, consumer will easily walk away, and when it is low-priced,a doubt about quality will aries. Price of a product or a service will, more often than not,affect consumerâ€™s buying decision. Thus it is important for a company to be able to place anacceptable price. Yet, so far only few researche evaluated â€œprice acceptanceâ€ as consequenceof customer satisfaction. This research aims to assess the relationship between price fairness,customer satisfaction, loyalty, and price acceptance in a service company. Questionnaireswere distributed to respondents by the self-administered questionnaire method and a total of187 completed questionnaires were used in the analysis. The data was then analzed usingstructural equation modeling. Three of five hypotheses were supported, and two others werenot supported. This paper alson provides the implications for theoritical and managerial andoffers directions for future research.Keywords : Price fairness, Customer Satisfaction, Loyalty, Price Acceptance